2019
DOI: 10.5530/fra.2019.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvent Polarity and Extraction Method on Phytochemical Composition and Antioxidant Potential of Corn Silk

Abstract: Objectives: Corn silk is an underutilized part of corn which possesses great medicinal importance. The present study was planned to determine the phytochemical composition and antioxidant potential of corn silk extracts, obtained by different extraction methods using a series of solvents with increasing polarity. Methods: Three extraction methods 1) individual extraction in each solvent, 2) consecutive extraction in solvents of increasing polarity and 3) consecutive extraction of crude methanolic extract in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
1
20
0
2
Order By: Relevance
“…Instead, in the TFC analysis, except for EtOH extract (194.00 ± 5.00 QE mg/g), both EtOAc (141.50 ± 10.00 QE mg/g) and MeOH (125.25 ± 1.25 QE mg/g) extracts were comparatively similar to the aqueous extracts (115.25 ± 6.25 QE mg/g). Previous studies have shown that aqueous plant extracts contain low levels of phenolics and flavonoids despite their higher yield, and organic extracts contain high levels of phenolics and flavonoids [ 26 , 29 ]. This observation is apparent in the ASE EtOH extract.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, in the TFC analysis, except for EtOH extract (194.00 ± 5.00 QE mg/g), both EtOAc (141.50 ± 10.00 QE mg/g) and MeOH (125.25 ± 1.25 QE mg/g) extracts were comparatively similar to the aqueous extracts (115.25 ± 6.25 QE mg/g). Previous studies have shown that aqueous plant extracts contain low levels of phenolics and flavonoids despite their higher yield, and organic extracts contain high levels of phenolics and flavonoids [ 26 , 29 ]. This observation is apparent in the ASE EtOH extract.…”
Section: Discussionmentioning
confidence: 99%
“…Allelopathy is a natural ecological function by which some organisms influence the activity of other organisms living in their surroundings. The influence is achieved by releasing secondary metabolites, also called allelochemicals [ 13 , 14 , 15 ]. The use of synthetic products is commonly discouraged due to their high cost and the ecological problems related to their usage.…”
Section: Introductionmentioning
confidence: 99%
“…An inquiry on corn silk from Multan Pakistan showed worthy phytochemical composition with a robust antioxidant activity. A polarity dependent rise in extracts yield, free radical scavenging action and phytochemical content of extracts reinforced with regression analysis of experimental data 68 . Z. mays seeds collected from Sahiwal Pakistan were screened for phytochemicals that showed coumarins, saponins, alkaloids, terpenoids and tannins.…”
Section: Zea Mays (Corn)mentioning
confidence: 78%
“…Phenolic compounds can also be extracted from corn silk extract of Zea mays and these constituents possess great antioxidant activity in nature 147 . Various researchers 68,69,70 documented the antioxidant potential of Z. mays from Pakistan. An inquiry on corn silk from Multan Pakistan showed worthy phytochemical composition with a robust antioxidant activity.…”
Section: Zea Mays (Corn)mentioning
confidence: 99%